1999
DOI: 10.1161/01.str.30.8.1561
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Anticardiolipin Antibody Titer Is a Stroke Risk Factor in a Multiethnic Population Independent of Isotype or Degree of Positivity

Abstract: Background and Purpose-Previous studies have produced conflicting results regarding the putative association between anticardiolipin antibodies (aCL) and infarction in the general stroke population. These inconsistencies may be a function of sample size and methodological differences among the studies. The purpose of the present study, the largest case-control study of this issue to date, was to assess aCL status as an independent risk factor for ischemic stroke in a multiethnic, urban population. Odds ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 20 publications
3
71
0
2
Order By: Relevance
“…In the largest case-control study to date (524 cases), IgG and IgM aCL antibodies were consistently associated with risk of cerebral ischemia 27 . Brey et al, in a recent controlled study involving 259 cases of ischemic stroke, reported that IgG aCL antibodies yielded a small risk (adjusted OR 2.2) for the outcome 28 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the largest case-control study to date (524 cases), IgG and IgM aCL antibodies were consistently associated with risk of cerebral ischemia 27 . Brey et al, in a recent controlled study involving 259 cases of ischemic stroke, reported that IgG aCL antibodies yielded a small risk (adjusted OR 2.2) for the outcome 28 .…”
Section: Discussionmentioning
confidence: 94%
“…Being IgM an antibody of acute response, the eventual presence of this isotype aCL might represent more the result than the cause of ischemic stroke. In previous controlled studies including the IgM aCL isotype 27,28 , the OR varied from significant to trivial.…”
Section: Discussionmentioning
confidence: 97%
“…Larger case-cohort studies have not consistently indicated higher prevalence of anti-cardiolipin antibodies among stroke compared to controls [122,123]. In another study, anti-cardiolipin antibodies were detectable in 11% of 1020 elderly controls without any clinical consequences [124]. Higher titers of anti-cardiolipin antibodies might not be associated with higher stroke recurrence risk [125].…”
Section: Thrombophiliamentioning
confidence: 99%
“…Image intensity is weighted by the relative oxygen level of blood hemoglobin (blood-oxygenation level dependent). 53 Contrast between images obtained during active and control task periods of a paradigm reflect changes in regional brain activity.…”
Section: Association Of Regional Brain Activity and Domains Of Neurocmentioning
confidence: 99%